2008
DOI: 10.1111/j.1365-2427.2008.01990.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of shoreline development on the nearshore environment in large deep oligotrophic lakes

Abstract: Summary 1. In large deep oligotrophic lakes, the shallow nearshore waters may provide the most important habitat for animals to feed and breed, and it is this area of the lake where humans are most likely to have initial impacts as the shoreline is developed. Nutrients in fertilizers, sediments and sewage effluents are likely to be rapidly intercepted by nearshore algae at the lake edge, having heterogeneous effects nearshore before offshore effects are noted. 2. Here we examined the spatially explicit effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
52
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 70 publications
(104 reference statements)
1
52
0
Order By: Relevance
“…In natural shore zones, nutrient inputs are controlled largely by the geological structure of the shore zone and its surroundings, but modern shore zones often are dominated by human inputs from sewage, urban and agricultural runoff, and atmospheric deposition. Even small changes in the inputs of phosphorus and nitrogen can affect the species composition and productivity of macrophytes and algae (e.g., Bertness et al 2002;Hecky et al 2004;Boers and Zedler 2008;Rosenberger et al 2008). …”
Section: Nutrientsmentioning
confidence: 99%
“…In natural shore zones, nutrient inputs are controlled largely by the geological structure of the shore zone and its surroundings, but modern shore zones often are dominated by human inputs from sewage, urban and agricultural runoff, and atmospheric deposition. Even small changes in the inputs of phosphorus and nitrogen can affect the species composition and productivity of macrophytes and algae (e.g., Bertness et al 2002;Hecky et al 2004;Boers and Zedler 2008;Rosenberger et al 2008). …”
Section: Nutrientsmentioning
confidence: 99%
“…Fortunately a variety of actions are available to property owners to mitigate the impact of development, such as selectively planting native vegetation or allowing remnant natural vegetation to grow in the near-shore zone * Corresponding author: amato@wisc.edu of their property and the littoral zone along it. The benefits of more natural shorelines may include increased plant diversity (Elias and Meyer 2003), reduced algae (Rosenberger et al 2008), higher numbers of animals such as frogs and native birds (Lindsay et al 2002, Woodford and Meyer 2003, Henning and Remsburg 2009, as well as larger and more abundant fish populations (Radomski andGoeman 2001, Helmus andSass 2008).…”
mentioning
confidence: 99%
“…In addition, human population growth and urbanization of rural areas have increased development pressure on lakes, and there is growing concern Understanding the consequences of residential development is therefore critical for understanding the ecology of lake ecosystems. A growing number of studies have found negative relationships between lakeshore development and water quality (Moore et al 2003); habitat structure (Christensen et al 1996, Jennings et al 2003, Francis and Schindler 2006; and population dynamics and community structure of primary producers (Radomski and Goeman 2001, Jennings et al 2003, Rosenberger et al 2008, macroinvertebrates (Banziger 1995, Brauns et al 2007, and fishes (Bryan and Scarneccia 1992, Jennings et al 1999, Schindler et al 2000, Radomski and Goeman 2001, Scheuerell and Schindler 2004, Sass et al 2006, Wagner et al 2006. These comparative studies provide much needed information linking shoreline development and key lake characteristics.…”
mentioning
confidence: 99%